Competence-Based Approach in the Context of the Implementation of Educational Standards in the Russian Language in Preschool Primary Education (Eurasian Journal of Learning and Academic Teaching, 2022)
Modern preschool primary education cannot remain aloof from the processes of modernization of education that are taking place today all over the world, including in Uzbekistan. For the initial link, as an important and integral stage of personality education, the use of a personality-oriented approach, informatization and competencebased approach, the emergence of which is associated with the demands of society and the needs of the individual in education, is characteristic. The purpose of the article is to consider the features, methods and techniques of the formation of the communicative competence of children in the process of primary language education